Occupational health practice. - Waldron, H. A. (Harry Arthur); Schilling, R. S. F. (Richard Selwyn Francis) (Butterworths, 1989)
Developments in occupational health; Pre-placement screening; Principles of toxicology; The introduction and monitoring of occupational diseases; Mental health of people at work; Vibration; Noise; Ionizing radiation; Thermal stresses in occupations; Biological monitoring of exposure to industrial chemicals; Pulmonary function and assessment; Audiometry; Vaccination policies; Principles of occupational epidemiology; Survey design; Atmospheric monitoring; Analytical methods; Sickness absence; Toxicity testing of industrial chemicals; Ergonomics; Protective clothing; Health effects on hyperbaric environments; Treatment and first aid services; Emergency medical treatment; Vocational rehabilitation and resettlement; Migrant workers; Special problems in developing countries; Health promotion and counselling.